Pelaksanaan Manajemen Strategi dan Kebijsakan dalam Peningkatan Mutu Pendidikan Agama Islam di SDIT Otoman Depok - Nurkaidah (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
This research is motivated by management strategies and policies to improve the quality of Islamic religious education in elementary schools, but the quality is still low. For schools to provide quality education, they need to develop comprehensive education management strategies. To realize the implementation of strategic management to improve the quality of Islamic religious education at SDIT Otoman, leaders and managers of educational institutions are needed. As leaders of educational institutions, school principals have an important role in improving the quality of education. The focus of this research is to analyze how management strategies and policies are implemented to improve the quality of Islamic religious education at SDIT Otman Depok. The aim of this research is to determine the implementation of management strategies and policies to improve the quality of Islamic religious education at SDIT Otman Depok. This research is a qualitative descriptive research. The research location was carried out at SDIT Otman Depok. Based on the results of SDIT Otman's research, the strategy and management of policies to improve the quality of Islamic religious education should go through three processes: (1) formulation through the formulation of the school's vision and mission, and (2) implementation, through the implementation of school policies and staff motivation. (3) Evaluation and control, including activities such as planning, implementation processes, monitoring activities, and activity results.